2019
DOI: 10.1002/jid.3431
|View full text |Cite
|
Sign up to set email alerts
|

Can Anthropologists Contribute to Road Construction? Insights from Southwest China

Abstract: This paper documents the contributions of anthropologists in the improvement of road construction in Yunnan Province of Southwest China. It argues that the involvement of social scientists in road planning can make important contributions to a people‐centred approach, advocate for cultural embeddedness and meet local needs, all of which help to avoid local conflict while promoting local ethnic culture. The policy implication drawn from this research calls for placing social sustainability at the forefront of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…First, the impact of infrastructure on the economy is fully reflected in the classical economic growth theory and is considered an indispensable element for economic growth (Donaldson and Hornbeck, 2016; Lucas, 1988). Secondly, the results on the impact of infrastructure on social development are also relatively rich, such as the effect of infrastructure on the health and happiness of residents (Harris et al, 2020), ethnic cultural integration (He and He, 2019), environmental protection (Boruszko et al, 2018) and inclusive growth (Mutiiria et al, 2020). Equity has always been the focus of research in the field of social development, and some scholars have found that the expansion of infrastructure (such as transportation infrastructure and public service infrastructure) is conducive to promoting social equity (Li et al, 2020).…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…First, the impact of infrastructure on the economy is fully reflected in the classical economic growth theory and is considered an indispensable element for economic growth (Donaldson and Hornbeck, 2016; Lucas, 1988). Secondly, the results on the impact of infrastructure on social development are also relatively rich, such as the effect of infrastructure on the health and happiness of residents (Harris et al, 2020), ethnic cultural integration (He and He, 2019), environmental protection (Boruszko et al, 2018) and inclusive growth (Mutiiria et al, 2020). Equity has always been the focus of research in the field of social development, and some scholars have found that the expansion of infrastructure (such as transportation infrastructure and public service infrastructure) is conducive to promoting social equity (Li et al, 2020).…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%